Optimization of cell culture conditions for the production of Newcastle disease virus - Mohd Azmir bin Arifin (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
The present work aims to prepare a model for the production of lentogenic Asplin F strain of Newcastle disease virus (NDV) using cell culture in bioreactor for live vaccine preparation. First NDV was adapted in four different cell lines namely DF-1, CEF, MSB-1 and Vero cells in T-flasks. DF-1 was found to be the most potential for NDV propagation in terms of high NDV production, rapid proliferation rate and several ethical values. Viruses produced in DF-1 cell culture were confirmed as lentogenic NDV strain by molecular diagnosis by using reverse transcriptase polymerase chain reaction (RT-PCR). In a screening experiment, high cell concentration during time of infection was found to be the most significant factor for NDV production. In another screening experiment, DF-1 was cultured in DMEM, DMEM-F12, RPMI 1640 and MEM. Culture of DF-1 cells in DMEM has the highest cell concentration of 1.240 × 106 cells/ml with specific growth rate and doubling time of 0.0180 h-1 and 38.4967 hours respectively. Composition of culture medium was later optimized and it was observed that culture has optimum cell concentration of 1.368 x 106 cells/ml when 2.1 g/L of NaHCO3 and 7.5% serum is included in the culture medium. Experiment was continued with culture of DF-1 cells in spinner vessel. In an optimization of microcarrier concentration study, culture with 3 g/L microcarrier achieved maximum cell concentration of 0.515 × 106 cells/ml compared to culture having 1 g/L, 2 g/L, 4 g/L and 5 g/L microcarriers. Based on this result and previous optimization studies, NDV was propagated in DF-1 cell culture in spinner vessel and the maximum virus titre achieved was 128 HA unit with infectivity titre of 3.08 x 107 TCID50/ml. In a separate experiment using 2-L stirred tank bioreactor, an optimization of process conditions study was conducted and it was analyzed that maximum cell concentration of 1.213 × 106 cells/ml will be obtained when the agitation rate is set at 71 rpm, microcarrier concentration at 2.9 g/L and pO2 pressure at 20%. NDV was also propagated in DF-1 cell culture in stirred tank bioreactor and the maximum virus titre achieved was 4 HA unit with infectivity titre of 1.03 x 103 TCID50/ml. Viruses produced from both types of bioreactors were later concentrated by using the high speed centrifugation method. An optimization study on process conditions of high speed centrifugation was conducted and it was revealed that optimum virus titre of 256 HA unit was achieved when the sample concentration was set at 50%, centrifugation speed was set at 12800 rpm and centrifugation time was set at 8 hours. The ability of cell culture in producing NDV in bioreactors has been shown in this study thus the model can be proposed for ND vaccine production in the future.